2019
DOI: 10.1177/0098628319834174
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Retrieval Practice Effects in the Classroom Using PeerWise

Abstract: The present study explored the generation and retrieval practice effects within a college classroom using a free, online tool called PeerWise (PW). PW allows students to create their own multiple-choice questions, share them with peers, and answer the shared questions written by their peers. Forty students from two sections of an upper level cognitive psychology course authored and answered multiple-choice questions as part of a semester-long assignment. Analyses showed reliable generation and retrieval practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Regardless of the question selection process, using published student-generated questions on high-stakes examinations introduces a concern that students who either authored or answered the questions prior to the exam may have an unfair advantage. There is evidence that students perform significantly better on subsequent exam questions if they have previously authored or answered questions that merely target the same topics (Kelley et al 2019). Similar research, which addresses a potential bias relating to topic-selection, has shown that these results are robust even when students are randomly assigned topics on which to author questions (Denny et al 2017).…”
Section: Two Approaches For Selecting Student-authored Questionsmentioning
confidence: 88%
“…Regardless of the question selection process, using published student-generated questions on high-stakes examinations introduces a concern that students who either authored or answered the questions prior to the exam may have an unfair advantage. There is evidence that students perform significantly better on subsequent exam questions if they have previously authored or answered questions that merely target the same topics (Kelley et al 2019). Similar research, which addresses a potential bias relating to topic-selection, has shown that these results are robust even when students are randomly assigned topics on which to author questions (Denny et al 2017).…”
Section: Two Approaches For Selecting Student-authored Questionsmentioning
confidence: 88%
“…Regardless of the question selection process, using published student-generated questions on high-stakes examinations introduces a concern that students who either authored or answered the questions prior to the exam may have an unfair advantage. There is evidence that students perform significantly better on subsequent exam questions if they have previously authored or answered questions that merely target the same topics (Kelley et al, 2019). Similar research, which addresses a potential bias relating to topic-selection, has shown that these results are robust even when students are randomly assigned topics on which to author questions (Denny et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Generating, solving, and evaluating questions are active tasks that promote various aspects of cognitive and metacognitive learning (Yu, Fu-Yun, 2012;Kelley, Chapman-Orr, Calkins, & Lemke, 2019;Kay, Hardy, & Galloway, 2020). Despite the importance of student question generation (SQG) and its associated activities, teachers do not tend to include it in their teaching, instead focusing students' attention on simply answering questions.…”
Section: Introductionmentioning
confidence: 99%